Development and Validation of Tafenoquine by HPLC Technique along with stress degradation study of Tafenoquine (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The most prevalent parasite disease in humans is malaria. According to estimates, 3 billion individuals worldwide are at danger of developing this illness. For the quantitative detection of tafenoquine, a brand-new, quick, and accurate stability-indicating high performance liquid chromatographic method was created and validated. On an Inertsil ODS-3V column (150 mm 4.6 mm, 5.0 m) with mobile phase methanol and water (80:20) at a flow rate of 1 mL/min, effective chromatographic separation was accomplished. The analyte was seen using a photo-diode array detector at a wavelength of 254 nm. Tafenoquine was subjected to acidic, basic, oxidative, thermal, and photolytic conditions in order to force its destruction. The peaks of the degradation products produced were distinct from those of tafenoquine and showed the specificity and stability of the technique. The method was also validated using criteria like specificity, precision, linearity, accuracy, and robustness in accordance with the International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use. The major goal of this research was to create a fast, sensitive, and stable HPLC method for analysing and assessing the purity and stability of tafenoquine in formulations.